Experimental investigation of filtration on a rotary nutsche - Machač, Ivan; Cakl, Jiří; Šiška, Bedřich (Univerzita Pardubice, 2000)
The filtering ability of a pilot plant cylindrical rotary nutsche (RN filter) has been tested on the basic of vacuum and pressure filtration experiments with suspensions of diatomite, magnesian limestone, and cellulose. The rotary nutsche is constructed like a circular drum with the bottom half being used as the filter area. The drum is placed on four wheels and simple rope drive enables the drum to oscillate. It is declared that this arrangement should possess several merits in comparsion with the classical nutsche. It was confirmed by results of filter tests that the filter can be used for anticipated applications with declared priorities following from principle of its construction. The results showed an evident dependence of filter performance and filter cake quality on the mode of filter drum rocking and the properties of solid.
Keywords: chemické inženýrství; filtrace; filtry; testování